Do we work hard or are we just great? The effects of organizational pride due to effort and ability on proactive behavior - Prisca Brosi; Matthias Spörrle; Isabell M. Welpe (Business Research, 2018)
This study derives a conceptual framework for examining parallel and differential influences of organizational pride in employees' efforts versus abilities on proactivity. Data from a field survey (N = 1218) confirm our theoretical model. Organizational pride in employees' efforts and organizational pride in employees' abilities both had positive indirect effects on proactive behaviors via affective organizational commitment. Yet, whereas organizational pride in employees' efforts additionally had a direct positive effect on individual and team member proactivity, organizational pride in employees' abilities showed a direct negative effect on proactive behaviors for the self, the team, and the organization including a behavioral measurement of employees' provision of ideas for improvement. These findings contribute to the nascent literature on organizational pride by indicating towards employees as source of organizational pride, highlighting potential negative effects of organizational pride, and introducing the differentiation between employees' efforts and abilities.
Keywords: 650; Organizational pride; Effort; Ability; Commitment; Proactivity